Cruella de Vil and The Fairy Godmother: Watching Disney with My Students - Martínez, Alejandra (2013)
In this article I reflect on the importance of critically analyzing the cultural products aimed at children. To achieve this kind of analysis my students and I have developed a performative exercise in which we have co-created a theatrical piece. A fragment of the script appears below where we appropriate and reconstruct the contents of children?s films from a critical point of view. For those who participated, this performance produced a transformation in our representations. The performative exercise highlights how, through critical analysis and performance, we are able to reconstruct those characters we have known and loved since childhood.